Effect of different swim caps on the assessment of body volume and percentage body fat by air displacement plethysmography - Peeters, M. W.; Claessens, A. L. (Journal of Sports Sciences, 2011)
Isothermal air trapped in scalp hair generates an underestimation of body volume when it is measured by air displacement plethysmography. The aim of this study was to examine the effect of wearing different types of swim caps on the measurement of body volume and percentage body fat by air displacement plethysmography. It was hypothesized that wearing a silicone swim cap would more thoroughly compress scalp hair compared with a lycra swim cap, yielding higher estimates of body volume and percent body fat. Thirty female participants aged 25.7 ± 6.4 years were measured in random order when wearing no swim cap, a lycra swim cap or a silicone swim cap. For the no-cap versus lycra cap condition, the mean bias for body volume was -0.579 ± 0.380 litre (limits of agreement: -1.340 to 0.181 litre) and for percent fat -4.9 ± 3.1% fat (limits of agreement: -11.2 to 1.3% fat) (P < 0.05). For the silicone versus lycra condition, the mean bias for body volume was 0.137 ± 0.099 litre (limits of agreement: -0.062 to 0.335 litre) and for percent fat 1.2 ± 0.9% fat (limits of agreement: -0.5 to 2.9% fat) (P < 0.05). In conclusion, attention should be paid to optimal compression of isothermal air trapped in scalp hair when using air displacement plethysmography. The present results suggest that this compression may be more thorough when wearing a silicone swim cap.